The Study of Parbhâsan Alos: Madurese Language Variation as Cultural Attitude by Santri Putri at Islamic Boarding School - Khofifatul Qulub; Jaftiyatur Rohaniyah; Dinar Vincy Yunitaka Bahrudin (Institut Agama Islam Negeri Palopo, 2025)
This study examines the sociolinguistic phenomenon of parbhâsan alos, a variation of Madurese language that reflects respect, politeness, and cultural attitudes among santri putri of Islamic Boarding School. Although a number of studies have discussed Madurese language in general, studies that specifically explore the role of language as a reflection of cultural attitudes in the Islamic boarding school environment, especially among santri putri, are still very limited. This study aims to understand how language variations are used as a reflection of social and cultural values in everyday life in the Islamic boarding school environment. The method used is descriptive qualitative with a case study design. Data were collected through non- participant observation, documentation, and field notes for two weeks. The results of the study indicate that bhâsa èngghi-bhunten is used when interacting with the caretaker of islamic boarding school, ustadz, and administrators of the Islamic boarding school; bhâsa engghi-enten is used in conversations between santri putri; while the bhâsa enjâ’-iyâ is used when interacting with younger people. The use of this language variation is influenced by the rules of the Islamic boarding school which require the use of polite and polite Madurese language in everyday life. For example, when one of a santri putri answer the call of the ustadz by saying,